Enterobius vermicularis Salpingitis Seen in the Setting of Ectopic Pregnancy in a Malaysian Patient - Romano, Ngui; Sarala, Ravindran; Diana Bee, Lan Ong; Tak, Kuan Chow; Kah, Pin Low; Syeda Nureena, Zaidi; Yamuna, Rajoo; Yuee, Teng Chin; Amirah, Amir; Arine Fadzlun, Ahmad; Yvonne Ai, Lian Lim; Rohela, Mahmud (American Society for Microbiology, 2014)
We report a rare and unusual case of invasive Enterobius vermicularisinfection in a fallopian tube. The patient was a 23-year-old Malaysian woman who presented with suprapubic pain and vaginal bleeding. A clinical diagnosis of ruptured right ovarian ectopic pregnancy was made. She underwent a laparotomy with a right salpingo-oophorectomy. Histopathological examination of the right fallopian tube showed eggs and adult remnants of E. vermicularis, and the results were confirmed using PCR and DNA sequencing.